Mechanistic Insights into the Regulation of the Spermatogonial Stem Cell Niche - Hess, Rex A. (2006)
Potential therapeutic use of stem cells in the treatment of human diseases depends on our ability to control the balance of their differentiation and self-renewal in vitro and in vivo. The stem cell “niche,” or specialized microenvironment, is now recognized as one of the major contributors to this regulation in many species. Our recent study, which was reported in Nature, was the first to demonstrate that expression of a vertebrate animal transcription factor is essential for the maintenance of a stem cell niche. In that letter, targeted disruption of ERM (ets-related molecule), which was localized only in the somatic support cell of the testis, the Sertoli cell, resulted in failure of self-renewal by spermatogonial stem cells, following the first wave of spermatogenesis. One of the more important conclusions drawn was the realization that regulation of the stem cell niche during the perinatal period, a phase characterized by rapid mitosis of both spermatogonial stem cells and Sertoli cells, differed from that in the adult. It appears that the ERM-regulated pathways are coincident with the termination of Sertoli cell proliferation and commencement of the cycle of spermatogenesis, which is sustained by the same cell that regulates the stem cell niche. Several likely targets for ERM regulation are discussed, as well as their potential implications for increasing our understanding of spermatogonial stem cell activity and the uniqueness of the Sertoli cell's immune privilege and possible utility for the protection of transplanted adult stem cells.